3D light painting robot - Zhu, Hongjiao (2016)
Since the creation of light painting in 1889, light painting has become a very popular trend these days due to the large amount of ownership of cameras and the huge impacts of sharing photos on social networks. Numerous of people start trying taking a light painting photo. 3D light painting is new level of light painting that create a more stunning three dimensional light painting photo. However creating a 3D light painting is extremely tedious. The purpose of this project is to ease the process of 3D light painting with computer programs and other technologies. This project successfully created a 3D light painting robot system that allows the user to take a 3D light painting photo with minimal effort. Users now only have to do some simple setups and the robot system will finish the rest of the 3D light painting job automatically. Although this project has achieved the objective, there are still many possibilities to improve the usability of this project in future.